PURWARUPA ROBOT TARI JAIPONG DENGAN MENGGUNAKAN KONTROLER CM-530 - Markus Dwiyanto Tobi; Yusuf Efendy (Electro Luceat, 2020)
Technological advances in the field of robotics have entered various aspects of human life ranging from automation in the fields of industry, military, entertainment, and in the medical field. Humanoid robot or humanoid robot is a form of technology implementation in the field of robotics that can mimic some human activities to walk and move several body organs like humans. The design of Jaipong Dance Robot based on CM-530 consists of a minimum system that functions as a controller of servo motor movement as a robot actuator and processes the data generated by the gyro sensor as a balance sensor. The design of Jaipong Dance Robot based on CM-530 has been successfully made and can work well, from standing movements, opening 1, opening 2, pencugan 1, pencugan 2, mincid kendor 1, pencugan 3, mincid kendor 2, mincid gancang 1, mincid gancang 2, mincid gancang 3, mincid gancang 4, nibakeun, dan mincid gancang 5, the success rate is 80%. Gyroscope GS-12 sensor can provide the desired balance point, the Dynamixel AX-12A Servo Motor as propulsion which is located at each joint of the jaipong dance robot, the Battery / Power Supply as the power provider.